A Study of Prevalence of Plantar Fasciitis in Zumba Exercisers - Kadari, Amani Anwarhusen; Doijad, Amruta; . Pathan, Umiya I (Journal of Neonatal Surgery, 2025)
Introduction: Plantar fasciitis is a common cause of heel pain, often resulting from excessive strain, repetitive stress, and biomechanical imbalances. Zumba, a high-impact aerobic dance workout, involves frequent jumping, pivoting, and rapid directional changes, which may contribute to plantar fascia strain. Despite the increasing popularity of Zumba, there is limited research on the prevalence of plantar fasciitis among its participants. Methodology: This study was conducted after the Ethical clearance was obtained from the Institution Ethical Committee. A cross-sectional observational study was conducted on 97 female Zumba participants aged 25–40 years with a BMI above 23 kg/m², training for more than three months. Data collection included demographic details, history of Zumba training, pain assessment using the Numerical Pain Rating Scale (NPRS), and diagnosis using the Windlass test. Result: The study found a prevalence of 53.61% for plantar fasciitis among Zumba exercisers. The mean age of participants was 32.91 years, with an average BMI of 29.11 kg/m2. The Windlass test, a clinical diagnostic tool for plantar fasciitis, showed 53.61% positive cases, indicating a high association between Zumba and foot-related stress injuries. Conclusion: The findings highlight a significant prevalence of plantar fasciitis in Zumba exercisers, suggesting that high-impact dance workouts contribute to foot strain and injury risk. Preventive measures such as stretching routines and weight management should be emphasized to reduce injury rates.